2018
DOI: 10.1101/469957
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proliferation Saturation Index in an adaptive Bayesian approach to predict patient-specific radiotherapy responses

Abstract: Purpose: Radiotherapy prescription dose and dose fractionation protocols vary little between individual patients having the same tumor grade and stage. To personalize radiotherapy a predictive model is needed to simulate radiation response. Previous modeling attempts with multiple variables and parameters have been shown to yield excellent data fits at the cost of nonidentifiability and clinically unrealistic results. Materials and Methods:We develop a mathematical model based on a proliferation saturation ind… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…In Figure 1 of the PSI model (Sunassee et al 2019), two cases are shown with detailed measurements of the volume of cancers using largely different k p and c D : For these patients, the agreements are very good. In Figure 2 of this paper (Sunassee et al 2019), they show comparisons of the PSI model with the common values of k p and c D by changing slightly the PSI values. The agreements are good.…”
Section: Cancer Stages Of Starting Treatmentmentioning
confidence: 90%
See 3 more Smart Citations
“…In Figure 1 of the PSI model (Sunassee et al 2019), two cases are shown with detailed measurements of the volume of cancers using largely different k p and c D : For these patients, the agreements are very good. In Figure 2 of this paper (Sunassee et al 2019), they show comparisons of the PSI model with the common values of k p and c D by changing slightly the PSI values. The agreements are good.…”
Section: Cancer Stages Of Starting Treatmentmentioning
confidence: 90%
“…Especially in the field of radiotherapy, it is remarkable to see various models trying to accommodate the biological radiation effect using the LQ model, which is expressed in terms of the total dose D to the t dependent dynamics due to the proliferation of tumor. These models are the ZM model and related works (Zaider and Minerbo 2000), the clinical model using the proliferation saturation index (PSI) (Rockne et al 2010;Prokopiou et al 2015;Tariq et al 2016;Sunassee et al 2019), and the clinical model using the biological effective dose (BED) (Fowler 1989(Fowler , 2010, together with many related works (Tobias 1985;Sottoriva et al 2010;Borasi 2016;Borasi & Nahum 2016).…”
Section: Comparison With Experimental Datamentioning
confidence: 99%
See 2 more Smart Citations
“…For clinical purpose, predictive models may not need to accurately describe the complex biology of cancer, but to provide a trigger for decision making, often upon binary endpoints. For many years, we have set ourselves the lofty goal of predicting the tumor burden evolution during treatment with ever decreasing error to the actual data [14–16]; yet the clinical endpoint for patients is often not the actual tumor volume dynamics but binary endpoints such as continuous response or cancer progression, tumor control or treatment failure. Machine learning approaches (or simple statistics) can identify threshold values for tumor burden at different time points during therapy that stratify patients into the different outcomes [17–19].…”
Section: Figurementioning
confidence: 99%